Prognosis and future developments in vasculitis. Issue 1 (February 2018) - Basu, N.; Karabayas, M.; Pusey, C.
Abstract: The prognosis of ANCA-associated vasculitis has been transformed in recent years. Once it was a set of invariably acute and fatal conditions, but these disorders are currently considered to be chronic diseases. This change is largely attributable to earlier diagnosis and the careful application of immunotherapeutics. However, patients still experience premature mortality, relapse, comorbid ill health and poor quality of life. Mortality rates in large-vessel vasculitis are not comparable; however, morbidity and poor patient outcomes prevail. Toxicity secondary to glucocorticoids represents a common driver of poor outcomes across systemic vasculitis. The main thrust of future treatment strategies is to reduce if not eliminate exposure to these agents.